Possibility of chest wall dose reduction using volumetric-modulated arc therapy (VMAT) in radiation-induced rib fracture cases: comparison with stereotactic body radiation therapy (SBRT). (22nd March 2018) - Murakami, Yu; Nakano, Masahiro; Yoshida, Masahiro; Hirashima, Hideaki; Nakamura, Fumiya; Fukunaga, Junichi; Hirose, Taka-aki; Yoshioka, Yasuo; Oguchi, Masahiko; Hirata, Hideki
Abstract: The present study compares dosimetric parameters between volumetric-modulated arc therapy (VMAT) and 3D conformal radiation therapy (3D-CRT) in lung tumors adjacent to the chest wall treated with stereotactic body radiation therapy (SBRT). The study focused on the radiation dose to the chest wall of 16 patients who had developed radiation-induced rib fractures (RIRF) after SBRT using 3D-CRT. The targets in all patients were partially overlapping with the fractured ribs, and the median overlapping rib–PTV distance was 0.4 cm. Stereotactic body radiation therapy was re-planned for all patients. The prescribed dose was 48 Gy in four fractions to cover at least 95% of the planning target volume (PTV). Evaluated dosimetric factors included D98% and the conformation number (CN) of the PTV, the D2cm 3, V40 and V30 of the fractured ribs, the V30 of the chest wall, and the Dmean, V20 and V5 of the lung. A comparison of 3D-CRT with the VMAT plan for PTV revealed that CN was significantly improved in the VMAT plan, whereas D98% did not significantly differ between the two plans. Regarding organs at risk (OARs), the D2cm 3, V40 and V30 of fractured ribs, the V30 of the chest wall, and the Dmean, V20 and V5 of the lung, were significantly decreased in the VMAT plan. We concluded that the dose to OARs such as ribs and chest wall could be reduced with improved target conformity using VMAT instead of 3D-CRT for SBRT to treat peripheral lung tumors.